2017
DOI: 10.1038/srep39991
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvic oxime dioxygenase from heterotrophic nitrifier Alcaligenes faecalis is a nonheme Fe(II)-dependent enzyme homologous to class II aldolase

Abstract: Pyruvic oxime dioxygenase (POD), a key enzyme in heterotrophic nitrification, was purified from Alcaligenes faecalis, and the molecular and catalytic characteristics were reexamined. POD was purified as the homotetramer of the subunit whose molecular weight was 30,000. The deduced amino acid sequence of POD was homologous with a class II aldolase that has been regarded as the Zn(II)-dependent enzyme catalyzing aldol reactions. The recombinant protein showed weak POD activity, and was activated by reconstitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Strain NS58 was cultivated aerobically in an (NH 4 ) 2 SO 4 -supplemented artificial seawater medium at 25°C in the dark (6). Genomic DNA of N. oceani strain NS58 was extracted using the DNeasy blood and tissue kit (Qiagen) and fragmented using the Covaris acoustic solubilizer, as previously reported (10). The library constructed using the TruSeq DNA PCR-free library prep kit (Illumina) was sequenced using the Illumina MiSeq platform (301-bp paired-end reads).…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain NS58 was cultivated aerobically in an (NH 4 ) 2 SO 4 -supplemented artificial seawater medium at 25°C in the dark (6). Genomic DNA of N. oceani strain NS58 was extracted using the DNeasy blood and tissue kit (Qiagen) and fragmented using the Covaris acoustic solubilizer, as previously reported (10). The library constructed using the TruSeq DNA PCR-free library prep kit (Illumina) was sequenced using the Illumina MiSeq platform (301-bp paired-end reads).…”
Section: Announcementmentioning
confidence: 99%
“…The resultant 799,711 high-quality read pairs, totaling 428 Mb and representing 122-fold coverage of the genome, were assembled using SPAdes ver. 3.13.0 (12) with a combination of the default set of k -mer sizes and options (–careful, –only-assembler, and –cov-cutoff auto), as previously described (10). The draft genome consisted of 54 contigs (>200 bp) totaling 3,508,376 bp with a G+C content of 50.33% and included one plasmid (designated pNS58) identical to the plasmid A (GenBank accession number CP000126) of ATCC 19707 T .…”
Section: Announcementmentioning
confidence: 99%
“…C. pauculus UM1, isolated from an agricultural soil sample in Hadley, MA, USA, is a phenol-degrading ( 3 ) copper- and nickel-resistant heterotrophic nitrifier ( 3 ) and denitrifier ( 4 ), capable of oxidizing both the carbon and nitrogen of pyruvic oxime ( 3 ). The enzyme responsible for pyruvic oxime oxygenation, pyruvic oxime dioxygenase (POD), has been cloned, characterized, and noted as a class II adolase ( 5 ). Recent work (D. Castignetti, unpublished data) has indicated that the POD of C. pauculus UM1 has significant nucleotide (75%) and amino acid homologies (85%) to the POD of the Alcaligenes faecalis isolate of Tsujino et al ( 5 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…The enzyme responsible for pyruvic oxime oxygenation, pyruvic oxime dioxygenase (POD), has been cloned, characterized, and noted as a class II adolase ( 5 ). Recent work (D. Castignetti, unpublished data) has indicated that the POD of C. pauculus UM1 has significant nucleotide (75%) and amino acid homologies (85%) to the POD of the Alcaligenes faecalis isolate of Tsujino et al ( 5 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“… 20 further proposed a pathway of heterotrophic nitrification where the hydroxylamine generated by the AMO reacts with pyruvate non-enzymatically; then the pyruvic oxime thus generated is decomposed by POD into nitrite and pyruvate. Subsequently, it has been shown that the pod gene encoding the enzyme is widely distributed in the bacteria of the phyla Proteobacteria and Actinobacteria, as well as in the eukaryotic microorganism of the phylum Ascomycota 21 .…”
Section: Introductionmentioning
confidence: 99%